2020
DOI: 10.3892/ijmm.2020.4495
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus salivarius BP121 prevents cisplatin‑induced acute kidney injury by inhibition of uremic toxins such as indoxyl sulfate and p‑cresol sulfate via alleviating dysbiosis

Abstract: The gut microbiota is important for maintaining the integrity of the intestinal barrier, promoting immunological tolerance and carrying out metabolic activities that have not evolved in hosts. Intestinal dysbiosis is associated with chronic kidney disease and probiotic supplementation has been shown to be beneficial. However, it is not known whether gut microorganisms-specifically, lactic acid bacteria (LAB) can protect against acute kidney injury (AKI). To address this issue, the present study investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 52 publications
(56 reference statements)
1
51
0
Order By: Relevance
“…Our results showed that Lactobacillus salivarius supplementation enhanced immune responses to infectious bursal disease vaccine in chickens with cy treatment. This may be due to Lactobacillus salivarius enhanced the body's ability to resist oxidative stress, which has been confirmed by previous studies (28,29), and our results are consistent with these findings. In addition, we also found that Lactobacillus salivarius group exhibited an enhanced immune response after immunization compared to control group in chickens without cy treatment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results showed that Lactobacillus salivarius supplementation enhanced immune responses to infectious bursal disease vaccine in chickens with cy treatment. This may be due to Lactobacillus salivarius enhanced the body's ability to resist oxidative stress, which has been confirmed by previous studies (28,29), and our results are consistent with these findings. In addition, we also found that Lactobacillus salivarius group exhibited an enhanced immune response after immunization compared to control group in chickens without cy treatment.…”
Section: Discussionsupporting
confidence: 93%
“…In addition to reduce the room temperature by spraying water, negative effects of heat stress can be alleviated by feeding anti-oxidative substances in poultry production ( 6 , 27 ). Previous studies have evaluated the antioxidant activity of various Lactobacillus strains and indicated that Lactobacillus salivarius showed good anti-oxidative properties ( 28 , 29 ). In the present study, Lactobacillus salivarius supplementation effectively alleviated the organ damage and enhanced anti-oxidative capacity in both acute heat stress and circular heat stress condition.…”
Section: Discussionmentioning
confidence: 99%
“…CKD patients are frequently associated with gut dysbiosis and the elevation of circulating indoxyl sulfate and PCS [ 14 , 44 ]. Probiotics or nutritional therapy are of benefit for improving gut dysbiosis and decreasing circulating uremic toxins, oxidative stress, and inflammation [ 6 , 45 ]. Since indoxyl sulfate and PCS remain difficult to remove by hemodialysis, gut microbiota could be an alternative target for reducing the circulating indoxyl sulfate, PCS levels, and their toxicity in CKD patients, with the aim of slowing down the progression of the disease and decreasing any CNS complications.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective cohort study, serum indoxyl sulfate levels were also associated with mortality in hospital-acquired AKI [ 14 ]. In a murine model, suppression of indole and p-cresyl production by Lactobacillus salivarius protected against cisplatin-induced kidney injury [ 23 ].…”
Section: Discussionmentioning
confidence: 99%